Analisis Kelayakan Bisnis pada Produk Sustainable Fashion untuk Mewujudkan SDGs Poin 12 dalam Perspektif Ekonomi Islam (Studi Kasus Produk Cariyos) - Aulia, Nadya Desi; Ridlwan, Ahmad Ajib (Institut Agama Islam Negeri Parepare, 2023)
The production and consumption of fashion products has increased significantly, which is in line with the increase in the garment industry on a large and small scale. The garment industry produces main waste, namely the remaining fabric of fashion production which can cause environmental damage, such as water pollution, soil pollution, and the production of greenhouse gas emissions which can cause climate change, so sustainable fashion can be the right solution. The purpose of this research is to analyze a business feasibility study through 5 aspects on sustainable fashion products, namely the Cariyos totebag, to support the SDGs goal at point 12. The results showed that based on the sharia business feasibility study on environmental aspects, technical and technological aspects, competitive aspects, market and marketing aspects and financial aspects, Cariyos products are said to be feasible to execute.